Analisis Diskriminan Pada Indikator yang Memengaruhi Indeks Kerentanan Pangan Menurut Kabupaten/Kota di Indonesia Tahun 2022 - Berliana, Rizka Widya; Fathony, Nyimas Syifa Dzulia Putri; Haryanto, Albertus Eka Putra; Wulandari, Sri Pingit (Politeknik Statistika STIS, 2023)
Food vulnerability is one of the keys to the second goal of the Sustainable Development Goals (SDGs). Food vulnerability is a condition of insufficient food to meet physiological needs standards. Food vulnerability in Indonesia will reach 4.85% in 2022. In fact, this figure has not yet reached the 2020-2024 target set by the Ministry of Agriculture of 4%. Therefore, it is necessary to predict food vulnerability in the future. One of the statistical methods that can be used to predict data with qualitative dependent and quantitative independent variables is discriminant analysis. This study uses secondary data from the official website of the food agency. The results of the study show that in the highly vulnerable districts/cities, the majority of households still do not use clean water. The test results show that there is a significant difference between the percentages (poverty, food expenditure, no electricity, no clean water, and stunting) with the three food vulnerability index categories. The percentage of poverty and households without clean water has the greatest contribution to food vulnerability with an accuracy of 82.43%.